Epidemiologic Behavior and Estimation of an Optimal Cut-Off Point for Homeostasis Model Assessment-2 Insulin Resistance: A Report from a Venezuelan Population. (29th October 2014) - Bermúdez, Valmore; Rojas, Joselyn; Martínez, María Sofía; Apruzzese, Vanessa; Chávez-Castillo, Mervin; Gonzalez, Robys; Torres, Yaquelín; Salazar, Juan; Bello, Luis; Añez, Roberto; Chacín, Maricarmen; Toledo, Alexandra; et al.
Abstract : Background. Mathematical models such as Homeostasis Model Assessment have gained popularity in the evaluation of insulin resistance (IR). The purpose of this study was to estimate the optimal cut-off point for Homeostasis Model Assessment-2 Insulin Resistance (HOMA2-IR) in an adult population of Maracaibo, Venezuela. Methods. Descriptive, cross-sectional study with randomized, multistaged sampling included 2, 026 adult individuals. IR was evaluated through HOMA2-IR calculation in 602 metabolically healthy individuals. For cut-off point estimation, two approaches were applied: HOMA2-IR percentile distribution and construction of ROC curves using sensitivity and specificity for selection. Results. HOMA2-IR arithmetic mean for the general population was 2.21 ± 1.42, with 2.18 ± 1.37 for women and 2.23 ± 1.47 for men (P = 0.466 ). When calculating HOMA2-IR for the healthy reference population, the resulting p75 was 2.00. Using ROC curves, the selected cut-off point was 1.95, with an area under the curve of 0.801, sensibility of 75.3%, and specificity of 72.8%. Conclusions. We propose an optimal cut-off point of 2.00 for HOMA2-IR, offering high sensitivity and specificity, sufficient for proper assessment of IR in the adult population of our city, Maracaibo. The determination of population-specific cut-off points is needed to evaluate risk for public health problems, such as obesity and metabolic syndrome.